Strengthening Students’ Civic Character through the Pancasila Student Profile Project in the Merdeka Curriculum: A Qualitative Study - Bongguk Haloho; Ulung Napitu; Corry Corry; Tuangkus Harianja; Maria Sonanggok (Newinera Publisher, 2026)
This study explored how the concept of the Pancasila Student Profile Project can be used within the framework of the Merdeka Curriculum and how it can be used to foster the development of the civic character of SMIP Universitas Simalungun students. Due to the perceived mismatches between moral teaching and practical implementation in civic education, a qualitative methodological approach was implemented to evaluate how the project-based learning and institutional practices were implemented in the enactment of character values. The data were gathered through the in-depth interview with school leaders and teachers, classroom observations, and institutional documentation analysis. Data were analyzed using an iterative coding and thematic interpretation to evoke patterns of pedagogical practice, engagement of students, and organizational support. Results indicate that before the project was carried out, civic learning was more theoretical and external thus constraining the internalization of moral values. Constant engagement in participative and situational learning processes contributed to the gradual enhancement of responsibility, social awareness and participatory confidence in the students. Some of the most important facilitators of this change were institutional coordination, reflective evaluation and collaboration among teachers. In addition, the element of the Simalungun local wisdom solidified the moral identity of the students by connecting the national civic principles to the traditionally based ethics. The research indicates that participatory pedagogy, unified institutional design, and culturally sensitive learning conditions are the conditions of the successful construction of civic character in the context of the Merdeka Curriculum.